2006
DOI: 10.1111/j.1365-2934.2006.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of an Integrated Care Pathway for all patients with advanced life-limiting illness ? the Supportive Care Pathway

Abstract: Unacceptable variations in care for those nearing the end of life is recognized. It is believed that the use of the Supportive Care Pathway may help to reduce that variation by identifying and supporting patients thought to be in the last year of their life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…According to Greenhalgh et al's (2004) model, support and advocacy from top management for the implementation process is vital for success. This was borne out in the literature, which showed that necessary resources were made available only with the approval or support of top management (Kitchiner & Bundred 1999;Jones & Johnstone 2004;Mellor et al 2004;Carr et al 2005;Ellershaw & Murphy 2005;Hockley et al 2005;Mirando et al 2005;Main et al 2006;Dawson et al 2007;Preston 2007;Taylor & Randall 2007;DHWA 2009;Edmonds et al 2009;Masso & McCarthy 2009).…”
Section: Theory Area 5: Resources (Context)mentioning
confidence: 99%
“…According to Greenhalgh et al's (2004) model, support and advocacy from top management for the implementation process is vital for success. This was borne out in the literature, which showed that necessary resources were made available only with the approval or support of top management (Kitchiner & Bundred 1999;Jones & Johnstone 2004;Mellor et al 2004;Carr et al 2005;Ellershaw & Murphy 2005;Hockley et al 2005;Mirando et al 2005;Main et al 2006;Dawson et al 2007;Preston 2007;Taylor & Randall 2007;DHWA 2009;Edmonds et al 2009;Masso & McCarthy 2009).…”
Section: Theory Area 5: Resources (Context)mentioning
confidence: 99%
“…The concept of 'preferred place of care' (irrespective of provider) is more important in longer term care planning for example in mental health 19 and end of life care. 20 On the face of it, the lack of a well-developed literature on the relationship between pathways and infrastructure seems like a strange omission. The concept of pathways invokes a geographical and spatial metaphor to understand health-care processes.…”
Section: Care Pathways and The Health Care-built Environmentmentioning
confidence: 96%
“…Within this context, the ICPAT has facilitated the development of the Supportive Care Pathway, an ICP for all patients with advanced life-limiting illness who are thought to be in the last year of life. 16 While the above indicates the translation of the development of ICPAT into the realities of developing ICPs, the potential contained within ICPAT has yet to be realized. The work of Vanhaecht et al 17 highlighted this potential, indicating within their evaluation how the ICPAT is the most appropriate clinical pathway audit tool to assess clinical pathway documents.…”
Section: The Icpat In Practicementioning
confidence: 97%